Pengaruh Arus Kas Bebas dan Efektivitas Komite Audit Terhadap Kualitas Audit - Ratu Gita Handayani; Cris kuntandi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Good audit quality is an important factor in ensuring the integrity and reliability of an entity's financial reports. This research aims to examine the influence of free cash flow and audit committee effectiveness on audit quality. Free cash flow reflects the availability of financial resources for a company to finance operational and audit activities. Meanwhile, an effective audit committee can ensure adequate oversight of the financial reporting and audit processes. This research uses panel data which includes companies listed on the Indonesia Stock Exchange during the 2018-2022 period. Free cash flow is measured using the ratio of operating cash flow to total assets, while audit committee effectiveness is measured using a composite score that includes the audit committee's independence, expertise and activities. Audit quality is assessed based on proxies such as the size of the public accounting firm, auditor industry specialization, and audit fees. The research results show that free cash flow and audit committee effectiveness have a significant positive influence on audit quality. Companies with high free cash flow tend to have adequate resources to pay higher audit fees, thereby encouraging auditors to carry out a more in-depth and quality audit process. In addition, an effective audit committee can ensure good oversight of the financial reporting and audit process, thereby improving audit quality. These findings provide important implications for companies and regulators in improving audit quality through managing free cash flow and establishing effective audit committees. Future research can explore other factors that influence audit quality and include relevant control variables.